2022
DOI: 10.1002/aur.2672
|View full text |Cite
|
Sign up to set email alerts
|

Intact fluency in autism? A comprehensive approach of verbal fluency task including word imageability and concreteness

Abstract: Verbal fluency is a cognitive function reflecting executive functions and the ability to retrieve the appropriate information from memory quickly. Previous studies reported conflicting results-impaired and intact verbal fluency-in autism spectrum disorder (ASD). Most studies concentrate on overall word productivity, errors, perseverations, clustering, or switching. We used a comprehensive approach to evaluate the reported discrepancy in the literature and introduced a new angle using the concept of word abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Interestingly, when group differences in TNCW were predicted but not discovered, some authors seemed doubtful that their findings could be generalized. For example, Tóth et al (2022) found no significant differences in TNCW between groups, and they acknowledge that their results replicated a lack of group difference reported by several previous studies. Rather than concluding that their results, combined with previous work, suggest unimpaired autistic verbal fluency skills, they write that this “might” be a “possibility,” but emphasize that “further studies [would be] required to… support this theory (p. 683).”…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Interestingly, when group differences in TNCW were predicted but not discovered, some authors seemed doubtful that their findings could be generalized. For example, Tóth et al (2022) found no significant differences in TNCW between groups, and they acknowledge that their results replicated a lack of group difference reported by several previous studies. Rather than concluding that their results, combined with previous work, suggest unimpaired autistic verbal fluency skills, they write that this “might” be a “possibility,” but emphasize that “further studies [would be] required to… support this theory (p. 683).”…”
Section: Discussionsupporting
confidence: 59%
“…Nine studies reported data specifically focused on the number of intrusions. Of these, six studies found no significant difference in the number of intrusions produced between groups (Begeer et al, 2014; Dunn et al, 1996; Foldager et al, 2022; Tóth et al, 2022; Turner, 1999; Zarokanellou et al, 2022), while two studies found the autistic group produced more intrusions than the comparison group (Dichter et al, 2009; Inokuchi & Kamio, 2013). Tang et al (2022) found only autistic individuals with a co‐occurring diagnosis of ADHD produced more intrusions than the comparison group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In ASD, studies have found reduced ( 74 76 ) or identical word count compared to control subjects in letter and semantic VFT ( 77 79 ). In contrast, the process-oriented measures of VFT, including clustering, switching, imaginability, and concreteness, did not differ from the NT controls ( 75 , 77 ). These discrepant findings may be due to the heterogeneity of ASD presentations ( 80 , 81 ).…”
Section: Introductionmentioning
confidence: 99%